Epithelial Cell Rests of Malassez Provide a Favorable Microenvironment for Ameliorating the Impaired Osteogenic Potential of Human Periodontal Ligament Stem Cells - Li, Yanjiao; Liu, Anqi; Zhang, Liqiang; Wang, Zhiwei; Hui, Nana; Zhai, Qiming; Zhang, Lishu; Jin, Zuolin; Jin, Fang (Frontiers in Physiology, 2021)
Human periodontal ligament stromal/stem cells (PDLSCs) are ideal candidates for periodontal regeneration and are of significant importance in clinical practice. However, PDLSCs derived from diseased microenvironments exert impaired behavior, which leads to the failure of periodontal regeneration. The epithelial cell rests of Malassez (ERM), which are involved in periodontal homeostasis, are residual cells from Hertwig’s epithelial root sheath (HERS). However, the function of ERM remains largely unknown. Therefore, the aim of this study was to evaluate the effect of ERM on the osteogenic potential of PDLSCs from an impaired microenvironment. PDLSCs from healthy donors (H-PDLSCs), periodontitis donors (P-PDLSCs) and human ERM were harvested. Osteogenic evaluation showed a lower osteogenic potential of P-PDLSCs compared to that of H-PDLSCs. Then, we cocultured ERM with P-PDLSCs, and the data showed that ERM promoted the expression of osteogenic genes and proteins in P-PDLSCs. In addition, we collected the PDLSCs from aged donors (A-PDLSCs) and analyzed the osteogenesis capacity of the A-PDLSCs and A-PDLSCs+ERM groups, which displayed similar results to P-PDLSCs. Finally, we evaluated the Wnt pathway, which is associated with osteogenic differentiation of stromal/stem cells, in A-PDLSCs+ERM and P-PDLSCs+ERM groups, which indicated that suppression of the Wnt pathway may result in an increase in the osteogenic properties of A-PDLSCs+ERM and P-PDLSCs+ERM groups. Taken together, the above findings shed new light on the function of ERM and provide a novel therapeutic for optimizing PDLSCs-based periodontal regeneration.